ICT Sector Policy Note for Panama : Enabling Inclusive Development through Information and Communications Technologies - World Bank (2015)
The Government of Panama and the private sector recognize the importance of information and communications technology (ICT) as an enabler of national development. This ICT sector policy note seeks to identify opportunities and challenges for growth of the ICT sector in Panama, particularly on rural access to broadband services and on cybersecurity, and potential for spillover impacts across other sectors. It provides a brief overview of the ICT sector in Panama and outlines a series of strategic actions and recommendations aimed at leveraging ICT as an engine of growth by targeting connectivity infrastructure, policies, regulation, e-Services, public data, and skills. The report is organized as follows: section one presents ICT sector in the economy. Section two deals with offer for connectivity. Section three presents demand. Section four describes the sector status from the cybersecurity point of view. Based on these analyses, section five identifies challenges that are hindering the growth of the industry, and section six presents policy options to overcome them. Finally, the World Bank describes the ways it can support those policy options in section seven and presents a set of joint activities in section eight.